Implementation of Electoral Service Policy in Fulfilling Voters' Constitutional Rights in the 2024 Local Elections in West Sumatra - Ory Sativa Syakban; Roni Ekha Putera; Ria Ariany (UNIVERSITAS PAKUAN, 2026)
This study analyzes the implementation of electoral service policies in fulfilling voters’ constitutional rights in the 2024 local elections in West Sumatra, Indonesia. Although voter service regulations have been established through General Election Commission regulations and technical guidelines, their implementation still reveals a gap between policy design and service delivery at the field level. This research employs a qualitative approach with a comparative case study in Padang City, Mentawai Islands Regency, and Sawahlunto City. These three locations were selected because they represent different territorial characteristics: a large urban area with low voter turnout, an archipelagic region with accessibility challenges, and a small city with high voter participation. The analysis is based on Edward III’s policy implementation theory, which consists of communication, resources, implementer disposition, and bureaucratic structure. The findings show that the implementation of electoral service policies has not been fully optimal. In terms of communication, technical information for voters and implementers was not always delivered evenly and consistently. Regarding resources, limitations in human resources, facilities, technology, and operational support affected service quality, particularly in geographically challenging areas. In terms of disposition, implementers generally demonstrated service commitment, but their responses to service constraints were shaped by field capacity and experience. Regarding bureaucratic structure, working procedures were available, yet coordination among actors was not fully effective. This study argues that the fulfillment of voting rights is not determined solely by regulatory completeness, but also by the administrative capacity of public institutions to provide electoral services that are accurate, inclusive, adaptive, and accessible.